2010
DOI: 10.1177/0731684409359545
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver Finishing of Composite Materials for EMSE

Abstract: In this work, copper core yarn (cotton sheath) was made into a plain fabric and treated with nanosilver particles. Copper (diameter 0.09 mm) was used as core material for producing Dref II core yarn with resultant count of 295 tex and core/sheath ratio 16/84. The cotton material is used as sheath. The Dref II friction spinning was used to produce the copper core yarn. In order to improve the electromagnetic shielding effectiveness of copper core yarn woven fabrics by nanosilver finishing, the copper core yarn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It can be divided in two main groups: surface treatments of textiles and special types of additives incorporated into textiles. The first group includes thin mono-or two-layer coats of metal such as Ag, Cu or Ni deposited on textile surfaces [4][5][6]. Such coats are prepared by various methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It can be divided in two main groups: surface treatments of textiles and special types of additives incorporated into textiles. The first group includes thin mono-or two-layer coats of metal such as Ag, Cu or Ni deposited on textile surfaces [4][5][6]. Such coats are prepared by various methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] Stainless steel, copper, silver, carbon yarn and their combinations, the effect of fabric parameters such as weave, ends per inch (EPI), picks per inch (PPI), number of fabric layers and diameter of copper yarns were also investigated by many researches for EM shielding effectiveness. 27 It was generally observed that increase in EPI, PPI and cover factor of fabric increase the SE from 350 up to 18,000 MHz. 12 Su and Chern 16 studied shielding behavior of conductive fabrics containing three different yarns namely cover, core, and plied yarns which consist of stainless steel as core and polyester as sheath.…”
Section: Introductionmentioning
confidence: 95%
“…À35 dB) and accepted reflection attenuation from about À4 dB to À15 dB for higher frequencies. Perumalraj et al 33 have studied the nano silver finishing of composite materials for EMSE. They observed that the EMSE of silver nano finished fabrics were improved by approximately 20-55% to that of the untreated copper core yarn fabrics.…”
Section: Introductionmentioning
confidence: 99%